Policy brief evaluation of exclusive breastfeeding program to improve infant health - Tiara Andhiny; Novrikasari Novrikasari; Anita Rahmiwati (Riset Informasi Kesehatan, 2026)
Background: Exclusive breastfeeding in Indonesia has yet to meet the 80% target set by WHO and the Ministry of Health. Coverage improved from 52% in 2017 to 66.1% in 2020 and reached 70.7% in 2022, but overall progress remains modest. Although national policies mandate exclusive breastfeeding, implementation is hampered by shortages of trained counselors, limited facilities, and cultural preferences for early formula feeding. Compared with neighboring countries, Indonesia is in the middle range, performing better than some but still behind regional leaders. To accelerate progress, stronger human resources, consistent workplace support, and greater community engagement are required to achieve national goals and contribute to global child health targets. Method: This study applied a literature review approach using the Google Scholar database. The initial search identified 3,080 articles, and after screening, only five studies (2020–2024, Indonesian language, full text, involving breastfeeding mothers) met the inclusion criteria. The selection stages were described with a PRISMA diagram. Results: Analysis showed that the most frequently reported barrier was the shortage of breastfeeding counselors, appearing in four of the five studies. Additional challenges included limited facilities, cultural habits such as early use of formula, and insufficient support from families and workplaces. Conclusion: The study concludes that limited breastfeeding counselors and weak family and workplace support are the main barriers, requiring stronger human resources and cross-sectoral collaboration.